Parenting Across Distance: An Exploration of OFW Parenting Style and the Young Adults’ Perspective - Samoling, Jhoniel; Daguinod, Kim Zhailock; Romualdez, Richielyn (International Journal of Education, Research, and Innovation Perspectives, 2026)
This study explored how Overseas Filipino Worker (OFW) parents practice parenting across distance and how their young adult children perceive these parenting efforts during long- term physical separation. Using a qualitative multiple case study design, the researchers conducted semi-structured interviews with ten OFW parent–child dyads and analyzed the data through Braun and Clarke’s thematic analysis. Findings revealed that OFW parents sustain their parenting roles through consistent digital communication, emotional reassurance, and intentional guidance, despite physical absence. Parents viewed their own parenting style as caring, authoritative, and grounded in sacrifice, resilience, and effortful involvement, adapting their approaches to remain patient, understanding, and emotionally available from afar. Young adult children generally perceived their parents as caring and authoritative, appreciating their sacrifices, though some reported experiences of permissiveness or emotional distance when communication was limited. Both groups emphasized that the quality of communication, more than its frequency, is central to maintaining emotional closeness. These findings highlight the importance of understanding parents’ perspectives and fostering emotional communication in OFW families, informing programs that support strong and healthy parent–child relationships across distance.